A modern roadmap for the use of simulation in regional anesthesiology training. Issue 5 (4th October 2022) - Kumar, Amanda H.; Sultan, Ellile; Mariano, Edward R.; Udani, Ankeet D.
Abstract : Purpose of review: A variety of educational modalities are used to teach regional anesthesia. Simulation is an educational tool that facilitates hands-on learning in a well tolerated, reproducible environment, eliminating potential harm to patients during the process of learning. Available literature and expert consensus statements support customizing simulation programs according to the level of training and experience of the learners. Recent findings: Simulation is useful for learners of all levels of expertise, though the application and frequency of simulation must be adapted to meet the learners' objectives. Summary: This review presents recommendations for the use of simulation for residents, fellows, practicing anesthesiologists without formal training in regional anesthesia, and practicing anesthesiologists with regional anesthesia expertise. Passports and portfolio programs that include simulation can be used to verify training. Virtual applications of simulation are growing, expanding the scope of regional anesthesia simulation and increasing access to lower resource areas.